Experimental noise-induced on-off intermittency in two bidirectionally-coupled diode lasers - Campos Mejía, Alfredo; Pisarchik, Alexander (Acta Universitaria, 2013)
Intermittent switches between chaotic and steady-state regimes are observed in experiments with two mutually-coupled diode lasers subject to common white gaussian noise. Both time series and power spectrum analyses yield typical scaling laws for on-off intermittency.